One‐Pot Synthesis of Highly Fluorescent Pyrido[1, 2‐a]indole Derivatives through CH/NH Activation: Photophysical Investigations and Application in Cell Imaging. Issue 44 (11th September 2014) - Samala, Srinivas; Pallavi, Pragyan; Kumar, Ravi; Arigela, Rajesh K; Singh, Gajendra; Ampapathi, Ravi Sankar; Priya, Amulya; Datta, Sunando; Patra, Abhijit; Kundu, Bijoy
Abstract We describe a straightforward strategy for the synthesis of strongly fluorescent pyridoindoles by Pd‐catalyzed oxidative annulations of internal alkynes with C‐3 functionalized indoles through CH/NH bond activation in a one‐pot tandem process. Mechanistic investigations reveal the preferential activation of NH indole followed by CH activation during the cyclization process. Photophysical properties of pyridoindoles exhibited the highest fluorescence quantum yield of nearly 80 %, with emission color varying from blue to green to orange depending on the substructures. Quantum mechanical calculations provide insights into the observed photophysical properties. The strong fluorescence of the pyrido[1, 2‐a]indole derivative has been employed in subcellular imaging, which demonstrates its localization in the cell nucleus.